2005
DOI: 10.1111/j.1740-0929.2005.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crushing unhulled rice and the addition of fermented juice of epiphytic lactic acid bacteria on the fermentation quality of whole crop rice silage, and its digestibility and rumen fermentation status in sheep

Abstract: This experiment was carried out to examine the effect of crushing unhulled rice and the addition of fermented juice of epiphytic lactic acid bacteria (FJLB) on the fermentation quality of whole crop rice silage, and its digestibility and rumen fermentation in sheep. After whole rice plants ( Oryza sativa L. cv. Haenuki) were harvested between the yellow and fullripened period of maturity, and cut at a length of 2 cm, four silage treatments were set: (i) non-treatment; (ii) crushing treatment of unhulled rice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 4 publications
4
32
0
2
Order By: Relevance
“…Buffering capacity was determined by the hydrochloric acid–sodium hydroxide method of Playne and McDonald . Ammonia‐N, lactic acid and volatile fatty acids were determined using the method of Shao et al To assess the quality of the silage, we calculated the V‐score from the NH 3 –N/Total N and VFAs concentrations . The mixed samples (10 g) were blended with 90 mL of sterilised water, and serially diluted in sterilised water.…”
Section: Methodsmentioning
confidence: 99%
“…Buffering capacity was determined by the hydrochloric acid–sodium hydroxide method of Playne and McDonald . Ammonia‐N, lactic acid and volatile fatty acids were determined using the method of Shao et al To assess the quality of the silage, we calculated the V‐score from the NH 3 –N/Total N and VFAs concentrations . The mixed samples (10 g) were blended with 90 mL of sterilised water, and serially diluted in sterilised water.…”
Section: Methodsmentioning
confidence: 99%
“…Butyric acid content (fresh weight basis) of added FJLB silage was substantially lower than that of non‐FJLB silage. Takahashi et al . (2005) reported that the lactic acid content increased and the fermentative characteristics tended to improve in whole crop rice silage with the addition of FJLB prepared from fresh rice straw.…”
Section: Resultsmentioning
confidence: 99%
“…Takahashi et al . (2005) reported that crude fiber and ADF digestibilities were improved by adding 1% FJLB prepared from fresh rice straw to the diet of sheep fed whole crop rice silage and commercial concentrate.…”
Section: Resultsmentioning
confidence: 99%
“…using a five‐point scale as follows: 1 (very bad), 2 (bad), 3 (moderate), 4 (good) and 5 (very good). Moreover, we also evaluated the quality of the silage with the V‐score method, calculating from the NH 3 ‐N/TN and VFAs concentrations . Briefly, V ‐ score = Y N + Y A + Y B , where Y N is calculated from the ratio of NH 3 ‐N/TN (% TN), Y A is calculated from the acetate plus propionate contents (% DM), and Y B is calculated from the butyrate content (% DM).…”
Section: Methodsmentioning
confidence: 99%